La competencia intercultural y el error pragmático - Tatoj, Cecylia (Studia Romanica Posnaniensia, 2021)
This paper discusses two topics which are very popular nowadays among the academics dealing with foreign language teaching, namely: intercultural competence and pragmatic error. The author notes the fact that those two notions appear separately, because the starting points for discussing them are usually different fields of science. The aim of the paper is to demonstrate that on one hand the two notions need to be treated uniformly, and on the other, that the pragmatic error should be included in error classifications which are references for both the authors of handbooks as well as people educating future teachers. For that purpose, the author defines intercultural competence, presents various approaches to error and its classification in teaching, and then explains what pragmatic error is and describes its linguistic characteristics.